INFLUENCE OF E-SERVICE QUALITY TOWARDS CUSTOMER LOYALTY IN THE SUBSCRIPTION VIDEO ON DEMAND (SVOD) SERVICE IN INDONESIA (CASE STUDY: NETFLIX) - Bachtiar, Muhammad Affan Huzairy; Chaerudin, Rendra (Journal of Business and Management, 2021)
Subscription video on demand (SVOD) seems to be getting popular as a choice of entertainment by consumers in the form of video such as movies and series including in Indonesia. SVOD can be accessed through the internet and can be accessed by many electronic devices connected to the internet. But with the rising of SVOD popularity, the competition in the industry became fierce with many new SVOD providers starting to spring up, and maintaining customer loyalty also becomes hard as companies trying to get as many customers as possible in the market therefore, it needs a strategy to maintain customer loyalty. The author chose to research how e-service quality can influence the customer loyalty of SVOD in Indonesia because SVOD is services provided on the internet and can be accessed either with web or app therefore e-service quality becomes an important factor to assess the service they provide. So, this research aims to see which e-service quality dimension has a significant impact on customer loyalty. The SVOD that became the object of this research is Netflix because they already have a long presence in Indonesia and have a substantial number of customers. Electronic service quality (E-service) quality is the ability of a company to provide service for customers through the online market. Customer loyalty is the commitment of customers to repurchase or patronize the same product and recommend it. The research is quantitative and was conducted by giving questionnaires to Netflix consumers in Jakarta and Bandung and the author managed to collect 110 data and analyze them with SEM-PLS method. The author found that e-service quality dimensions which are: Product portfolio, Information quality, visual appeal, and ease of use have a significant and positive influence on customer loyalty of Netflix customers in Indonesia.Keywords: E-service quality, Customer loyalty, (Subscription video-on-demand) SVOD, Netflix